2020
DOI: 10.1186/s13019-020-01346-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine on intraoperative Surgical Pleth Index in patients undergoing video-assisted thoracoscopic lung lobectomy

Abstract: Background The Surgical Pleth Index (SPI) is a monitoring method that reflects painful stimuli during general anesthesia, and dexmedetomidine is an analgesic adjuvant with an opioid-sparing effect. But up to now, it is still unclear whether dexmedetomidine has any influence on SPI. To investigate whether dexmedetomidine has an effect on SPI during video-assisted thoracoscopic surgery. Methods We enrolled 94 patients who underwent video-assisted thoracoscopic lung lobectomy. Patients were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The six studies were published between 2016 and 2020, and the total sample size was 510. Dexmedetomidine was used before the anesthesia [7,15,22,23], or during surgery [16,17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The six studies were published between 2016 and 2020, and the total sample size was 510. Dexmedetomidine was used before the anesthesia [7,15,22,23], or during surgery [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…However, the e cacy of dexmedetomidine supplementation for thoracoscopic surgery has not been well established. Recently, several studies on the topic have been published, and the results were con icting [7,[15][16][17]. With accumulating evidence, we therefore perform a systematic review and meta-analysis of RCTs to investigate the analgesic e cacy of dexmedetomidine supplementation for thoracoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Technologies/parameters used for monitoring the nociception-antinociception balance [59][60][61][62][63][64][65][66]. ANI -analgesia nociception index; qNOX index -index of nociception; qCON index -index of consciousness; SPI -Surgical Plethysmographic Index; NOL index -Nociception Level Index One of the most widely studied technologies is the analysis of hemodynamic changes and includes the evaluation of the normalized heart beat intervals (HBIs) and of the amplitude of the plethysmographic waves, both correlating with sympathetic and parasympathetic tones.…”
Section: Figurementioning
confidence: 99%
“…Table 2 summarizes a series of studies regarding the impact of monitoring techniques on the nociception-antinociception balance and on the clinical outcome of patients. Numerous studies have shown that opioid overdose during anesthesia is responsible for a series of adverse effects, such as increased recovery times and opioid induced hyperalgesia, and they also lead to hypotension, having a major impact on perioperative hemodynamic stability [66][67][68][69][70][71]. Won et al, have reported that using SPI monitoring during general anesthesia reduces opioid consumption, improves hemodynamic stability, and reduced postoperative recovery times [71].…”
Section: Figurementioning
confidence: 99%
“…Figure 1. Technologies/parameters used for monitoring the nociception-antinociception balance [59][60][61][62][63][64][65][66] One of the most widely studied technologies is the analysis of hemodynamic changes and includes the evaluation of the normalized heart beat intervals (HBIs) and of the amplitude of the plethysmographic waves, both correlating with sympathetic and parasympathetic tones. A higher sympathetic tone correlates with the intensity of the surgical stimuli and results in a suppressed plethysmographic amplitude (PPGA).…”
Section: Monitoring Techniques For the Nociception-antinociception Bamentioning
confidence: 99%